La expresión artística y el pensamiento lógico matemático en niños de 5 a 6 años de la Unidad Educativa José Ángel Palacio de la ciudad de Loja, periodo 2022-2023 - Torres Huanca, Saydi Arleth (2023)
Mathematical logical thinking develops skills that allow children to interact with their environment, being able to reason and reflect on any situation of interest, becoming creative beings using associations and mental operations to construct numerical concepts. The objective of this study was to determine how artistic expression strengthens mathematical logical thinking in children aged 5 to 6 years from the Unidad Educativa José Ángel Palacio in the city of Loja, period 2022-2023. It was framed in a quasi-experimental design, with a mixed approach that allowed the collection and analysis of qualitative-quantitative data and a descriptive scope, in addition, the methods were used: inductive-deductive and analytical-synthetic, present throughout the research. The technique used was observation, which helped to directly verify the results obtained in the activity guide. The Early Mathematical Assessment Test (EMAT) was used as an instrument, applied to nineteen children, showing that most of the sample presented deficiencies in the development of logical mathematical thinking, since 77.64% were at the moderate, low and very low level, because they showed problems in comparison, classification, correspondence, serialization, verbal counting, structured, resulting and general knowledge of numbers; After the execution of the activity guide using artistic expression, the difficulties were reduced to 51.97% at the moderate and low levels, highlighting that no child remained at the very low level, emphasizing that they strengthened in grouping, differentiation, order and understanding of basic concepts of counting, number, as well as notions, shapes and color. Concluding that it is possible to improve mathematical logical thinking through artistic expression used in its various manifestations such as dance, music, literature, theater, drawing and painting in an innovative way. Keywords: Artistic, expression, mathematical logic, high school.